Leoligin-inspired synthetic lignans with selectivity for cell-type and bioactivity relevant for cardiovascular disease12. Issue 22 (14th May 2019) - Linder, Thomas; Liu, Rongxia; Atanasov, Atanas G.; Li, Yuanfang; Geyrhofer, Sophie; Schwaiger, Stefan; Stuppner, Hermann; Schnürch, Michael; Dirsch, Verena M.; Mihovilovic, Marko D.
Abstract : The first total synthesis of the edelweiss constituent leoligin is reported, together with the first pharmacological evaluation of the parent compound and some of its analogs. Abstract : Recently, a natural compound leoligin, a furan-type lignan, was discovered as an interesting hit compound with an anti-inflammatory pharmacological activity profile. We developed a modular and stereoselective approach for the synthesis of the edelweiss-derived lignan leoligin and used the synthetic route to rapidly prepare leoligin analogs even on the gram scale. Proof of concept of this approach together with cell-based bio-assays gained structural analogs with increased selectivity towards vascular smooth muscle versus endothelial cell proliferation inhibition, a major benefit in fighting vascular neointima formation. In addition, we identified the structural features of leoligin analogs that define their ability to inhibit the pro-inflammatory NF-κB pathway. Results are discussed in the context of structural modification of these novel synthetic lignans.